Perbandingan Pendidikan Politik Partai Golkar dalam Meningkatkan Perolehan Suara pada Pemilu 2019 dan 2024 - Nur Habibah, Salma Zulfa; Tsabitah Aldjabri, Rachel Hisanaah; Ayu, Nia Rafa; Susilo, Galang Putra; Hanifan, Hafiz Zaki (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2025)
This study compares the role of political education conducted by the Golkar Party in increasing vote acquisition during the 2019 and 2024 general elections. It employs a descriptive qualitative method, using primary data from interviews with internal Golkar Party sources and secondary data from literature reviews. The findings show that in the 2019 election, Golkar’s political education remained conventional, elitist, and limited in scope. In contrast, the 2024 election saw the adoption of more modern and participatory strategies, including the use of social media, the establishment of the Golkar Institute, and collaboration with the General Elections Commission (KPU) through the "Rumah Pintar Pemilu" program. Although there was an increase in vote share from 12.31% to 15.29%, the study concludes that political education was not the sole determining factor in this improvement, and its effectiveness as the main driver remains limited. These findings highlight the importance of political education in strengthening democracy, but emphasize that it must be supported by principles of inclusivity, sustainability, and continuous evaluation to foster more meaningful and higher-quality political participation.